Effects of lead on performance and nutrient quality of two cowpea varieties (2003)
The effects of lead on plant growth, yield and nutrient quality of two cowpea varieties (IT94K-4403 and IT93KZ-8-21-23-3) were studied. Soil and seeds analyses for lead before planting and after harvest revealed variable decreases in lead levels in contaminated soil after harvest. While lead was not detectable in the planted and harvested seeds. There were no significant differences in the various lead contamination levels with respect to germination days and maturation days. Lead contamination was found to have adverse effects on the yield of cowpea. The variety IT94K-4403 showed no variation in protein after harvest with the different levels of lead contamination, IT93KZ-8-21-23-3 on the other hand showed variable deceases in protein content.